The Indigenous Lens? : Early Photography in the Near and Middle East. - Ritter, Markus (Studies in theory and history of photography., 2017)
The historiography of early photography has scarcely examined Islamic countries in the Near and Middle East, although the new technique was adopted very quickly there by the 1840s. Which regional, local, and global aspects can be made evident? What role did autochthonous image and art traditions have, and which specific functions did photography meet since its introduction? This collective volume deals with examples from Iran, the Ottoman Empire, and the Arab lands and with the question of local specifics, or an „Indigenous lens." The contributions broach the issues of regional histories of photography, local photographers, specific themes and practices, and historical collections in these countries. They offer, for the first time in book form, a cross-section through a developing field of the history of photography.